EXTREME POWER POINT TRACKER OF A LARGE PHOTOVOLTAIC SYSTEM BATTERY CHARGE CONTROLLER & REDUCING WEATHER EFFECT (International Journal of Scientific Research and Management (IJSRM), 2013)
Photovoltaic cells have a complex relationship between their operating environment and the maximum power they can produce. It shows non-linear I-V characteristics and that vary with solar insolation, environmental situation, age of the cell. This paper describes an efficient way for real time tracking of the maximum power point (MPPT) of a solar panel charging a battery in a varying weather. To estimate the maximum power that a cell can provide with an optimal load under any weather condition, selection of a controlling method is imperative. MPPT performance will be evaluated through ORCARD and a Prototype to have simulation and experimental results respectively.